2013
DOI: 10.1103/physrevd.88.083532
|View full text |Cite
|
Sign up to set email alerts
|

Astrophysics of Bertrand space-times

Abstract: We construct a model for galactic dark matter that arises as a solution of Einstein gravity, and is a Bertrand space-time matched with an external Schwarzschild metric. This model can explain galactic rotation curves. Further, we study gravitational lensing in these space-times, and in particular we consider Einstein rings, using the strong lensing formalism of Virbhadra and Ellis. Our results are in good agreement with observational data, and indicate that under certain conditions, gravitational lensing effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 37 publications
2
50
0
Order By: Relevance
“…Here, we have critically examined the delicate nature of the definition of circular velocity in a GR context, and showed that conventional definitions that are often used in the literature may not be very useful from a practical point of view. We argued that a phenomenological definition given in [8], [9] might be more effective in comparing with experimental data, in the context of Bertrand space-times, which we propose as a viable space-time metric seeded by galactic dark matter. We also commented on the spectroscopic interpretation of the formula for the rotation curve for BSTs.…”
Section: Galactic Rotation Curves and Bstsmentioning
confidence: 99%
See 4 more Smart Citations
“…Here, we have critically examined the delicate nature of the definition of circular velocity in a GR context, and showed that conventional definitions that are often used in the literature may not be very useful from a practical point of view. We argued that a phenomenological definition given in [8], [9] might be more effective in comparing with experimental data, in the context of Bertrand space-times, which we propose as a viable space-time metric seeded by galactic dark matter. We also commented on the spectroscopic interpretation of the formula for the rotation curve for BSTs.…”
Section: Galactic Rotation Curves and Bstsmentioning
confidence: 99%
“…However it should be clear from the preceding discussion that on doing this, fitting with observational data for galactic rotation curves becomes difficult (for example, the maximum value of the circular velocity in this case becomes c/(2 √ 2), an unrealistically large number). The resolution of this problem is to match an internal BST with an external Schwarzschild solution, as discussed in section 2 of [8]. However, this often results in the presence of a thin shell of matter near the matching radius, and in such situations, analytical handle on the problem might pose problems.…”
Section: Galactic Rotation Curves and Bstsmentioning
confidence: 99%
See 3 more Smart Citations